Attitude and Knowledge of the Parents of Neonates admitted with Tetanus Neonatorum - S. Dibjosubroto; M. Ruskandi; M.S. Azhali (Indonesian Pediatric Society, 1978)
Knowledge and attitude of 44 parents of neonates admitted with tetanus neonatorum to the Department of Child Health, Dr. Hasan Sadikin General Hospital, Bandung, from January 1975 through April 1976 were evaluated. Twenty-eight (63.7%) cases with tetanus neonatorum were from illiterate and elementary-school educated parents. Fourteen (31.8%) parents were aware of the mode of injection and 12 (27.3%) realized the importance of prevention of the disease; 10 (22.7%) mothers did not join prenatal care; 40 (90.9%) neonates were delivered by